ChemInform Abstract: Copper‐Catalyzed Cascade Reactions of N‐(2‐Bromoallyl)amines with KHCO3 as the C1 Source: An Efficient Process for the Synthesis of Oxazolidin‐2‐ones. Issue 5 (February 2015) - Jin, Hongwei; Yang, Yukun; Jia, Jianhong; Yue, Binjie; Lang, Bo; Weng, Jianquan
Abstract The reaction can be scaled up.